Feasibility and operationalisation of an investment promotion entity (IPE) for sustainable forest management-highlights from the main papers - Chipeta, M.E.; Joshi, M. (Center for International Forestry Research, 2001)
This synthesis paper was prepared based on key findings and issues of two separate papers and the highlighted issues included are:(1) Should the international community proceed with the Investment Promotion Entity (IPE) idea, and if so, what steps are needed to promote partnerships and other forms of co-operation with private party? (2) Given that private-sector fund managers are likely to invest only in developing countries with lowest risk and the most stable investment environments, how can IPE work to ensure that the benefits reach many of the poorest countries in greatest need of investment, and how can the public international sector assist in this regard? (3) At the currently suggested scale, the IPE may not effectively begin to satisfy the level of need. How can the IPE be made to raise new and additional funds rather than diverting existing assistance, and how can the volume of investments made through this new proposed instrument be increased? (4) Is there support for the idea of establishing the IPE at the global level, with a possibility of establishing regionally oriented IPEs later on, and for hosting regional IPEs at regional multilateral development banks?